Associações de espécies de peixes em ambientes lóticos da bacia do rio Iguatemi, Estado do Mato Grosso do Sul - Súarez, Yzel Rondon [UNESP] (2003)
The aim of this paper is to describe the patterns of associations between fish species and their distribution in lotic habitats at basin level. Samples were accomplished in 27 localities of Iguatemi river basin, distributed in four environments (Iguatemi river, Jogui river, Puitã river and streams). The presence/absence data of those species which occurred in 2 or more sites were submitted at multivariate methods with the aim to describe the major species associations. The species distribution was considered determinative in these communities (C-score = 17,33; P = 0,000), with significant difference among the studied environments (ANOSIM r = 0,082; P = 0,012), with verified difference between Iguatemi river and streams (P = 0,001) and also streams and Jogui river (P = 0,014). We verified a strong segregation among species from headstreams and more discharge river stretches or even larger streams.